Event-Related Potentials Altered in Patients with Borderline Personality Disorder during Working Memory Tasks - Liu, Ying; Zhong, Mingtian; Xi, Chang; Jin, Xinhu; Zhu, Xiongzhao; Yao, Shuqiao; Yi, Jinyao (Frontiers in Behavioral Neuroscience, 2017)
Whereas some studies have demonstrated impaired working memory (WM) among patients with borderline personality disorder (BPD), these findings have not been consistent. Furthermore, there is a lack of neurophysiological evidence about WM function in patients with BPD. The goal of this study was to examine WM function in patients with BPD by using event-related potentials (ERPs). An additional goal was to explore whether characteristics of BPD (i.e., impulsiveness and emotional instability) are associated with WM impairment. A modiﬁed version of the N-back task (0- and 2-back) was used to measure WM. ERPs were recorded in 22 BPD patients and 21 age-, handedness-, and sex-matched healthy controls while they performed the WM task. The results revealed that there were no significant group differences for behavioral variables (reaction time and accuracy rate) or for latencies and amplitudes of P1 and N1 (all p > .05). BPD patients had lower P3 amplitudes and longer N2 latencies than healthy controls, independent of WM load (low load: 0-back; high load: 2-back). Impulsiveness was not correlated with N2 latency or P3 amplitude, and no correlations were found between N2 latency or P3 amplitude and affect intensity scores in any WM load (all p > .05). In conclusion, the lower P3 amplitudes and longer N2 latencies in BPD patients suggested that they might have some dysfunction of neural activities in sub-processing in working memory, while impulsiveness and negative affect might not have close relationship with these deficits.